2008
DOI: 10.1021/np8003003
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Asterric Acid Derivatives from the Antarctic Ascomycete Fungus Geomyces sp.

Abstract: Five new asterric acid derivatives, ethyl asterrate (3), n-butyl asterrate (4), and geomycins A-C (6-8), have been isolated from cultures of an isolate of the Antarctic ascomycete fungus Geomyces sp. The structures of these metabolites were elucidated by NMR spectroscopy. The absolute configuration of 8 was determined by application of the CD excitation chirality method. Compound 7 displayed antifungal activity against Aspergillus fumigatus, whereas 8 showed antimicrobial activities against gram-positive and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…2009). Additional metabolites have been isolated from P. pannorum including antimicrobial asterric acid derivatives called “geomycins”, which is active against Aspergillus fumigatus , as well as Gram-positive and Gram-negative bacteria (Li et al 2008). …”
Section: Representative Cold-adapted Fungal Speciesmentioning
confidence: 99%
“…2009). Additional metabolites have been isolated from P. pannorum including antimicrobial asterric acid derivatives called “geomycins”, which is active against Aspergillus fumigatus , as well as Gram-positive and Gram-negative bacteria (Li et al 2008). …”
Section: Representative Cold-adapted Fungal Speciesmentioning
confidence: 99%
“…Geomycin B ( 52 ) showed significant antifungal activity against Aspergillus fumigatus ATCC 10894, with IC 50 /MIC values of 0.86/29.5 μM (the positive control fluconazole showed IC 50 /MIC values of 7.35/163.4 μM). Geomycin C ( 53 ) displayed moderate antimicrobial activities against the Gram-positive bacteria ( Staphylococcus aureus ATCC 6538 and Streptococcus pneumoniae CGMCC 1.1692) and Gram-negative bacterium ( Escherichia coli CGMCC 1.2340) [39]. …”
Section: Microorganismsmentioning
confidence: 99%
“…Bioactive, natural products from organisms from the perennially cold and dry climate of Antarctica have shown effective antimicrobial activity (Cavicchioli et al 2002;Zeng et al 2008). For example, bioactive asterric acid derivatives from the Antarctic ascomycete fungus (Li et al 2008), extracts from five Antarctic lichens (Paudel et al 2008), and 22 (3.8%) of 580 bacterial isolates from terrestrial as well as from water column along the Antarctic Terra Nova Bay (Ross Sea) exhibited strong antibacterial activity against a number of Gram-negative and -positive bacterial isolates such as Escherichia coli, Proteus mirabilis, Micrococcus luteus, Staphylococcus aureus and Bacillus subtilis. To our knowledge, no study has been reported on the antimycobacterial activity of pigments from Antarctic bacteria.…”
Section: Introductionmentioning
confidence: 99%